Applying Maqasid Sharia Principles to Sustainable Halal Supply Chains in Developing Countries - Musyafa (Generate Digital Publishing, 2025)
Objective: This research is expected to provide deeper insights into how applying maqasid sharia principles can support sustainable, ethical, and environmentally friendly business practices while meeting the needs of a growing market. Research Design & Methods: This study uses a qualitative research design and systematic literature review to analyze data from academic sources, focusing on Maqasid Sharia, sustainability, and the halal industry in developing countries. Findings: Companies that have adopted these principles are better able to respond to sustainability challenges and are more committed to social and environmental responsibility. Further discussions highlighted the importance of collaboration between governments, halal certification bodies, and the private sector in strengthening regulations and creating frameworks that support sustainability. Implications & Recommendations: These findings suggest that by improving regulatory and infrastructural support and providing access to necessary technologies, the halal industry in developing countries can be more globally competitive and contribute positively to society and the environment. Contribution & Value Added: Implementing maqasid sharia is expected to establish ethical business practices and encourage broader sustainability in the halal industry.